A novel and simple microwave hydrothermal method for preparation of CoAl2O4/sepiolite nanofibers composite. Issue 18 (15th December 2019) - Wang, Fei; Gao, Peizhang; Liang, Jinsheng; Zhang, Tingting; Zhang, Hui; Ding, Youpeng; Xu, Tianze; Fang, Baizeng
Abstract: A blue and bright CoAl2 O4 nanocomposite is fabricated by the microwave hydrothermal synthesis at the optimum conditions (pH = 13, 240 °C, 4 h, 15:1 of the metal salt to sepiolite). More interestingly, a significant improvement in the distribution of the supported CoAl2 O4 nanoparticles can be realized through the strategy of microwave hydrothermal coupled with surface modification by surfactants, which results in significantly improved suspension performance. The synthesis strategy is believed to provide a guide for the fabrication of supported nanocomposites with a uniform particle size for diverse applications such as heterogeneous catalytic reactions, ceramic materials, water-based coatings, and so on.